From Jerusalem to Irian Jaya : a biographical history of Christian missions - Tucker, Ruth, 1945- (Grand Rapids, MI Zondervan, 2004)
A revised edition of a highly acclaimed textbook on the history of Christian missions.--From publisher's description.
The irresistible advance. -- The early centuries : evangelizing the Roman Empire -- Roman Catholic missions : baptizing the masses -- American Indian missions : seeking the "noble savage" -- The Moravian advance : dawn of Protestant missions -- The "great century". -- South Central Asia : confronting ancient creeds -- Black Africa : "the white man's graveyard" -- China : "barbarians not welcome" -- The Pacific Islands : preaching in "paradise" -- The Muslim world : mission field in the desert -- Korea and Japan : a contrast in receptivity -- The expanding involvement. -- Single women missionaries : "second-class citizens" --
Includes bibliographical references (pages 513-514) and indexes.
Keywords: Missionaries -- Biography; Missions -- History; Biographies